Thermodynamic performance comparison of Organic Rankine Cycle between zeotropic mixtures and pure fluids under open heat source. (1st June 2018) - Su, Wen; Hwang, Yunho; Deng, Shuai; Zhao, Li; Zhao, Dongpeng
Highlights: A comprehensive performance comparison is conducted between mixtures and pure fluids. Simulation models are developed for basic ORC and recuperative ORC. Cycle efficiency (8.18%) of optimal R600a/R601a is lower than that of R601a (8.24%). Optimal R600a/R227ea has lower exergy efficiency (34.61%) than R227ea (35.68%). Mixture with a larger temperature glide generally recovers more heat of exhaust gas. Abstract: Zeotropic mixtures have been widely investigated for the development of Organic Rankine Cycle (ORC) as an alternative option for pure fluids. However, few zeotropic mixtures have been applied to the ORC in practical engineering. Therefore, a nature question is that whether zeotropic mixture has better thermodynamic performance of ORC than pure fluid. In this contribution, a comprehensive performance comparison between zeotropic mixtures and pure fluids is conducted via cycle simulation for the basic ORC and recuperative ORC driven by open heat source. In the simulation, a certain range of mass flow rate of cooling water is considered as the condition of heat sink, and mixtures R600a/R601a, R600a/R227ea are employed. Performances of these mixtures are optimized and compared with those of their constituents from the points of first and second laws. It can be concluded that zeotropic mixture may have lower cycle performance than pure fluid. For the optimal mixture R600a/R601a (0.1/0.9, mass fraction) with the highest net power of basic ORC, the cycle efficiency 8.18% is lower than that of R601a 8.24%. Although zeotropic mixture generally has lower temperature differences in the evaporator and condenser, the exergy losses of these heat exchangers are not certain to be reduced. In the basic ORC, the exergy efficiency 34.61% of optimal R600a/R227ea (0.2/0.8, mass fraction) is lower than that of R227ea 35.68%. Furthermore, the introduction of internal heat exchanger (IHE) can enhance the output work and cycle efficiency. The exergy loss in the evaporator and condenser can be reduced by IHE. The mixture with a larger temperature glide can generally recover more heat in the IHE.